Optimization of Pc-200 Excavator Productivity in Runway Excavation Work at Sta 0+000 - 0+700 Pohuwato Airport Development Gorontalo - Aldam Apriyansah, Mohammad; Winiasri, Linda; Suryono, Wiwid (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The implementation of the Pohuwato Airport construction project on excavation work requires heavy equipment Excavator to excavate the Runway body which will be installed geotextile. The purpose of using this heavy equipment is to facilitate work and streamline work time. The selection of heavy equipment must be carried out carefully and precisely so that the effectiveness in its use is optimal, and costs and time can be adjusted. This research was conducted at the construction of the Pohuwato airport in Imbodu village, Randangan sub-district, Pohuwato district, Gorontalo province, in this study using several alternative experiments to find the efficient value of implementation time and operational costs. This study uses several research methods, namely the productivity test of tools and field observations. Based on the calculation of the results of productivity analysis, it is found that alternative 3 is the most efficient result with working hours of 10 hours, using 6 units of excavators capable of producing 1,296 m³ per day with a total operational cost of Rp.14,873,200 per day. per day, alternative 3 is able to complete work with a volume of 56000 m³ for 43 days or 6 weeks, faster than field conditions with 2 excavator units can be completed for 108 days at a total cost of Rp. 8,247,840, while in alternative 1 using 3 excavator units can complete for 72 days at a total cost of Rp. 10,647,840, in alternative 2 using 3 excavator units can complete for 72 days at a total cost of Rp. 10,647,840. on alternative 2 using 3 units of excavators can complete for 96 days with a total cost per day of Rp. 7,985,880.